Thermo-mechanical modelling of structural battery composites - Svensson, Natasha (My University, 2020)
Industries are searching for energy efficient zero-emission transport solutions to minimise environmental impact from transportation [1]. A possible solution to this can be the use of structural battery composites which combines the ability to take mechanical load while also store electrical energy [1], i.e. combining the functionalities of structures and batteries. The aim of this thesis is to develop a model which can predict the thermo-mechanical behaviour of a laminated structural battery composite. It is conducted in collaboration with an other master’s thesis which instead focus on the battery modelling [2]. The laminated structural battery composite studied in this project has a similar structure to a regular Li-ion battery. The simplified model, made in comsol, was constructed as a three-layered battery unit cell where each layer’s properties was approximated by using composite micro-mechanics models. The boundary conditions were such that only the top boundary was allowed to move while having a convective heat flux applied. As the behaviour is only modelled (numerical investigation), i.e. no manufacturing or testing was conducted on real batteries, there is no way to know how good the modelled prediction actually compares to the reality. Instead investigation is made as a sensitivity study, to see how different parameters change the outcome which includes time, generated heat in the battery cell, heat transfer coefficient of the heat flux and thicknesses of the different layers. The results show that after some time a steady state temperature will be reached as long as the heat transfer coefficient is non-zero. This steady state temperature is important for future thermal experiments as a too low temperature will give misleading results. This thesis has though shown that it can be controlled by changing e.g. the generated heat from the battery cell by changing the C-rate or the heat exchange with the surroundings. The conclusion is therefore that this developed framework, in combination with the collaborated thesis [2], can be used to guide future experiments on the thermo-mechanical behaviour of a laminated structural battery composite.
Keywords: Structural battery composite; comsol; Finite Element; composite mechanics; thermal-mechanical behaviour